Extensive Cryptic Diversity in the Terrestrial Diatom Pinnularia borealis (Bacillariophyceae) - Pinseel, Eveline; Kulichová, Jana; Scharfen, Vojtěch; Urbánková, Pavla; Van de Vijver, Bart; Vyverman, Wim (Protist, 2019)
With the increasing application of molecular techniques for diatom species discovery and identification, it is important both from a taxonomic as well as an ecological and applied perspective, to understand in which groups morphological species delimitation is congruent with molecular approaches, or needs reconsideration. Moreover, such studies can improve our understanding of morphological trait evolution in this important group of microalgae. In this study, we used morphometric analysis on light microscopy (LM) micrographs in SHERPA, detailed scanning electron microscopy (SEM), and cytological observations in LM to examine 70 clones belonging to eight distinct molecular lineages of the cosmopolitan terrestrial diatom Pinnularia borealis. Due to high within-lineage variation, no conclusive morphological separation in LM nor SEM could be detected. Morphological stasis due to the "low-morphology" problem or stabilizing selection, as well as parallel/convergent evolution, phenotypic plasticity and structural inheritance are discussed as potential drivers for the observations. Altogether, P. borealis is truly cryptic, in contrast to the majority of other diatom species complexes which turned out to be pseudo-cryptic following detailed morphological analysis.
Keywords: rozsivky; Biodiversity; LSU rDNA; Microscopy, Electron, Scanning; shape.; Microscopy; morphometrics; Diatoms; molecular phylogenies; mikroskopie; biodiverzita; rbcL; mikroskopie elektronová rastrovací